2019
DOI: 10.1002/jbm.b.34496
|View full text |Cite
|
Sign up to set email alerts
|

Titania nanotube morphologies for osseointegration via models of in vitro osseointegrative potential and in vivo intramedullary fixation

Abstract: As total joint replacements increase annually, new strategies to attain solid bone‐implant fixation are needed to increase implant survivorship. This study evaluated two morphologies of titania nanotubes (TiNT) in in vitro experiments and an in vivo rodent model of intramedullary fixation, to simulate joint arthroplasty conditions. TiNT surfaces were prepared via an electrochemical etching process, resulting in two different TiNT morphologies, an aligned structure with nanotubes in parallel and a trabecular bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The diameter of nanotubes (Table 1) was selected as it provided the most compact coverage of the titanium surface and the lowest nano-roughness (36.5 nm for both types of NTs, Table 1) compared to other studies published on electrochemically etched titanium nanotubes, for example, 170 to 220 nm 33 or 172 to 348 nm. 34 Wide range of studies discussed the effect of NTs diameter on cell behavior, 22,[35][36][37] so choose a diameter of around 100 nm as the most potent diameter improving the adhesion and proliferation of fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The diameter of nanotubes (Table 1) was selected as it provided the most compact coverage of the titanium surface and the lowest nano-roughness (36.5 nm for both types of NTs, Table 1) compared to other studies published on electrochemically etched titanium nanotubes, for example, 170 to 220 nm 33 or 172 to 348 nm. 34 Wide range of studies discussed the effect of NTs diameter on cell behavior, 22,[35][36][37] so choose a diameter of around 100 nm as the most potent diameter improving the adhesion and proliferation of fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The surface modification induced by the nanotube structures combined with annealing can change the hemocompatibility of TiO 2 NTs, by alleviating platelet activation (Mazare et al [111,150], Junkar et al [15], Huang et al [192], Gong et al [193], Bai et al [191,194]). Several in vivo studies have shown that TiO 2 nanotubular layers could induce successful peri-implant bone formation/osseointegration in various animal models using different diameter NTs: von Wilmowsky et al (30 nm diameter nanotubes) [195], Wang et al (30,70, and 100 nm diameter NTs) in minipigs [174], Alves-Rezende et al (≈ 74 nm diameter NTs) [196], Baker et al (TiO 2 NTs-in vitro and in vivo intramedullary fixation) in rats [197], or the review of Wang et al [198] for the effect of TiO 2 NTs grown on the implants' surface on osseointegration in animal models.…”
Section: Tailoring Osteoinduction With Anodicmentioning
confidence: 99%
“…Although TNTs can effectively promote the osteogenic activity of bone-forming cells or preosteoblasts, it remains unclear whether these inferences are consistent under in vivo conditions. Baker et al [ 16 ] proposed that TNTs can stimulate bone marrow cell differentiation in vitro and promote bone regeneration and bonding strength in rodents. However, Sanchez et al [ 17 ] observed no significant differences between the use of TNTs and polished titanium after 30 days of healing in rodents.…”
Section: Introductionmentioning
confidence: 99%